Subclavian and axillary arterial aneurysms: two case reports - Esteves,Fernando Pinho (2013)
Aneurysms of the subclavian-axillary segment are rare, but when diagnosed they must be treated. This article describes two cases of aneurysms of the upper extremities, one in a subclavian artery and the other in an axillary artery. The first case was a 71-year-old male with a pulsating supraclavicular bulge on the right and muscle weakness in the ipsilateral extremity. Duplex scanning and arteriography confirmed the diagnosis of aneurysm of the right subclavian artery and the patient underwent aneurysmectomy and end-to-end anastomosis. The second case was a 24-year-old female patient, with no history of comorbidities, who presented with a pulsating mass in the right axillary region and paresthesia of the ipsilateral extremity. Duplex scanning and arteriography confirmed an aneurysm in the right axillary artery, which was successfully treated with aneurysmectomy and end-to-end anastomosis. Pathology findings showed that the first case was an atherosclerotic aneurysm and the second was a congenital aneurysm.